The level of awareness of hibah among Muslim residents in Raub, Pahang / Siti Norisshah Ghalid and Muhamad Zuhaili Saiman - Ghalid, Siti Norisshah; Saiman, Muhamad Zuhaili (Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi MARA (UiTM), 2023)
Hibah is an act of gifting a person which is permissible in Islam yet is not widely practised by Muslims in this country. Many Malaysians lack an understanding of the concept of Hibah due to insufficient knowledge and limited exposure to its implementation. Despite this, various insurance companies are actively promoting Hibah. This study aims to determine the understanding of the concept of Hibah among residents in Raub, Pahang, and assess the level of awareness of Hibah among Muslims. The research methodology employed a quantitative approach, utilizing a questionnaire survey to collect data from 327 respondents in Raub, Pahang. The findings indicate that the respondents are familiar with Hibah and intend to implement it for their heirs in the future. The study identifies understanding the concept of Hibah, awareness, attitude, and intention as contributing factors to the observed level of awareness. This paper fills a gap in the literature on Hibah, which lacks comprehensive studies in this area. The results offer valuable insights for counsellors, administrators, educators, future researchers, students, and individuals interested in the field of Hibah.